Middle East peace talks at the end of the road? One-state reality consolidating - Muriel Asseburg (Stiftung Wissenschaft und Politik (SWP), 2014)
The nine months of negotiations agreed last summer by the US mediators and the two parties ended on 29 April 2014. US Secretary of State John Kerry has since announced a pause in US facilitation activities. Yet, a definitive breakdown or failure of the Middle East peace talks bears far-reaching risks. Even if the mediators were to succeed in effecting a restart of talks, there is scant hope of bridging the rifts within the year envisaged - at least if the previous approach were to be maintained. That will lead to a further consolidation of the one-state reality that has long since emerged between the Mediterranean and River Jordan. Germany and its partners in the European Union must face up to the alternatives: either a much more robust approach to propel the talks to a two-state solution, or insistence on equal political, economic and cultural rights for all in the territories controlled by Israel. (SWP Comments)
Keywords: 320